Análisis e incidencia de la proyección de la película la Miel de las Morojas, entre los estudiantes de la carrera de comunicación social de la Universidad Nacional de Loja, periodo marzo-julio 2011. Lineamientos alternativos - Torres Motoche, Danny Fabricio (2016)
This work was developed with the primary purpose of developing the abilities and skills that young people, to create audiovisual products, linked to the film industry. Determined and defined the issue, we proceeded to approach the issue, which was discussed and noted that students of the School of Social Communication need production bases, production and distribution of a film product. Against this arises the following problem: What is the impact of the release of the movie "Honey of Morojas" among students studying in Social Communication from the National University of Loja? Each of the targets was verified based on the survey of students of the School in question, by a sample of the universe to investigate. This descriptive and exploratory research, character possible to state the views expressed in the work, for it was used methods: scientific, inductive, deductive, comparative and qualitative. Similarly, the survey and interview techniques, we have obtained results for hypothesis testing and verification of targets were used. Consequently it came to conclusions and recommendations, thus it was possible to have a broader study of the problem of knowledge; therefore, it was determined the need for a guide, to enable students of the School of Social Communication and independent filmmakers; know how to make the dissemination of film products running. The proposal contains appropriate formal means of communication, communication strategies adding more diffusion mechanism for unconventional means such as the web.